Customers for life : how to turn that one-time buyer into a lifetime customer - Sewell, Carl. 4 0 16; Brown, Paul B.; 5 (New York : Pocket Books, 1990)
An approach to customer service to achieve a competitive advantage.
Adult.
Keywords: 2 -- 0; 6; Customer services -- Customer service.;Automobile industry and trade;Automobile dealers;Automobile industry. -- United States.;United States; 20; 2